Circulating Epigenetic Biomarkers in Malignant Pleural Mesothelioma: State of the Art and critical Evaluation - Ferrari, Luca; Carugno, Michele; Mensi, Carolina; Pesatori, Angela Cecilia (Frontiers in Oncology, 2020)
Malignant pleural mesothelioma (MPM) is a rare and aggressive cancer, which originates from the mesothelial cells of the pleura and is associated with asbestos exposure. In light of its aggressive nature, late diagnosis and dismal prognosis, there is an urgent need for identification of biomarkers in easily accessible samples (such as blood) for early diagnosis of MPM. In the last ten years, epigenetic markers, such as DNA methylation and microRNAs (miRNAs), have gained popularity as possible early diagnostic and prognostic biomarkers in cancer research. The aim of this review is to provide a critical analysis of the current evidences on circulating epigenetic biomarkers for MPM and on their translational potential to the clinical practice for early diagnosis and for prognosis.